Multimodal Transport System Coevolution Model Based on Synergetic Theory - Fenling Feng; Qingya Zhang (Discrete Dynamics in Nature and Society)
This study investigates multimodal transport system evolution law with the consideration of synergetic theory. Compared with previous studies, this paper focuses on understanding influencing factors of system collaborative development. In particular, we have applied a multimodal system order parameter model to obtain the order parameter. Based on order parameters, the coevolution equations of the multimodal transport system are constructed with consideration of cooperation and competitive relationship between the subsystems. We set out the multimodal system followed the coevolution law of the freight system and dominated by the combined effects of order parameter line length and freight density. The results show that the coordination effects between railway, road, and water subsystems are stronger than aviation subsystem; the railway system is the short plank of the system. Some functional implications from this study are also discussed. Finally the results indicate that expansion of railway system capacity and mutual cooperation within the subsystems are required to reach an optimal multimodal transport system.